Indications and technical aspects of proximal gastrectomy - Kolozsi, Peter; Varga, Zsolt; Toth, Dezso (Frontiers in Surgery, 2023)
According to the World Health Organization, gastric cancer is the fifth most common type of tumor, and is the third most common cause of tumor-associated death. Although gastric cancer incidence rates have decreased in the past few decades, the prevalence of proximal gastric cancer has been steadily rising in developed countries. Techniques regarding the improvement of treatment options must thus be developed. This can be achieved through incorporating both a wider use of endoscopic surgery (endoscopic mucosal resection—EMR, endoscopic submucosal dissection—ESD) and a review of applied surgical interventions. Even though there is no single international consensus available, the Japanese Gastric Cancer Association (JGCA) recommends proximal gastrectomy with D1+ lymphadenectomy in early gastric tumors. Despite recommendations from Asian guidelines and the short term outcomes of the KLASS 05 trial, surgical treatments in Western countries still rely on total gastrectomy. This is mostly due to technical and oncological challenges regarding surgical interventions in a proximal gastrectomy. However, the residual stomach after a proximal gastrectomy has been shown to diminish the incidence of dumping syndrome and anemia, and even improve postoperative quality of life (QoL). Therefore, it is necessary to define the place of proximal gastrectomy in the treatment of gastric cancers.